PEMEROLEHAN BAHASA PADA ANAK KAJIAN ANTARA NURTURE DAN NATURE (Kasus “Wanita Tarzan” Kamboja) - Heri Kustomo (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
language acquisition factor plays an important role in the study of psycholinguistics. This does not mean to invalidate the study materials other areas of psycholinguistics. The crucial issue is still a matter of debate in language acquisition is a matter of nurture and nature. Respective sides of the theory of language acquisition it has strong arguments as a weapon to ward off attacks from the opposing party. News of the discovery of